Distal C Terminus of CaV1.2 Channels Plays a Crucial Role in the Neural Differentiation of Dental Pulp Stem Cells - Ge, Jianping (Public Library of Science, 2013)
L-type voltage-dependent CaV1.2 channels play an important role in the maintenance of intracellular calcium homeostasis, and influence multiple cellular processes. C-terminal cleavage of CaV1.2 channels was reported in several types of excitable cells, but its expression and possible roles in non-excitable cells is still not clear. The aim of this study was to determine whether distal C-terminal fragment of CaV1.2 channels is present in rat dental pulp stem cells and its possible role in the neural differentiation of rat dental pulp stem cells. We generated stable CaV1.2 knockdown cells via short hairpin RNA (shRNA). Rat dental pulp stem cells with deleted distal C-terminal of CaV1.2 channels lost the potential of differentiation to neural cells. Re-expression of distal C-terminal of CaV1.2 rescued the effect of knocking down the endogenous CaV1.2 on the neural differentiation of rat dental pulp stem cells, indicating that the distal C-terminal of CaV1.2 is required for neural differentiation of rat dental pulp stem cells. These results provide new insights into the role of voltage-gated Ca2+ channels in stem cells during differentiation.